RUSSIAN POPULATION'S ENTREPRENEURIAL ACTIVITY: AN INTERREGIONAL DIFFERENCES'S COMPARATIVE ANALYSIS - E. Popovskaya (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper deals with comparing of early-stage entrepreneurial activity level among Russia's regions. Such a comparison is becoming possible on the base of microdata of research project "Early-stage entrepreneurial activity in Russia: regional measurements" that has been realised in the National State University Higher School of Economics.